2019
DOI: 10.1002/jcu.22736
|View full text |Cite
|
Sign up to set email alerts
|

The role of the right atrium in development of postoperative atrial fibrillation: A speckle tracking echocardiography study

Abstract: Purpose Atrial fibrillation (AF) is relatively frequent in the postoperative period, and is associated with an increased frequency of adverse events. The role of right atrial (RA) volume and functions in the development of AF is unknown. In this study, we investigated the effect of RA echocardiographic indices on AF development in the postoperative period. Method We enrolled 142 consecutive patients who underwent coronary artery bypass surgery, and assigned them into two groups depending on the occurrence or n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 30 publications
2
19
1
Order By: Relevance
“…In addition, impaired diastolic Ca 2+ reuptake into the SR leads to reduced SR Ca 2+ load and a subsequent reduction in systolic Ca 2+ release, thereby providing a cellular correlate for the clinical observation that atrial contractile dysfunction is an independent risk factor for the development of poAF. 12 , 13 Based on our findings we propose that reduced SERCA activity is a common cellular mechanism underlying both impaired contractile function and atrial arrhythmogenesis.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…In addition, impaired diastolic Ca 2+ reuptake into the SR leads to reduced SR Ca 2+ load and a subsequent reduction in systolic Ca 2+ release, thereby providing a cellular correlate for the clinical observation that atrial contractile dysfunction is an independent risk factor for the development of poAF. 12 , 13 Based on our findings we propose that reduced SERCA activity is a common cellular mechanism underlying both impaired contractile function and atrial arrhythmogenesis.…”
Section: Discussionmentioning
confidence: 69%
“…Finally, reduced SERCA2a expression may contribute to preoperative atrial contractile dysfunction observed in patients developing poAF, 12 , 13 thereby linking atrial contractile dysfunction and atrial arrhythmogenesis. Atrial mechanical dysfunction has recently been suggested as a key determinant of atrial cardiomyopathy, a term describing an atrial phenotype which may promote the occurrence of adverse consequences such as thromboembolic stroke independent of AF.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They provides the clues for the mechanism of AF in pulmonary hypertension or chronic obstructive pulmonary disease could be right atrial enlargement with substantial increase in atrial mass (Medi et al, 2011(Medi et al, , 2012. Aksu et al (2019) also showed RA volume and functions are closely associated with AF development in the postoperative patients. Wen et al (2017) demonstrated that right atrial diameter (RAD) could be a prediction of arrhythmia recurrence after catheter ablation of AF.…”
Section: Right Atrial Fibrillation (Raf) and Right Atrialmentioning
confidence: 86%
“…So the right atrium should be an important part of the heart in atrial fibrillation process, and ablation only on the pulmonary vein would be non-responsive in the patients that excitation wavefronts and focal activity were on the right side from the beginning (Medi et al, 2011(Medi et al, , 2012Burnett and Kocheril, 2014;Hayashi et al, 2015;Hasebe et al, 2016Hasebe et al, , 2018Uemura, 2016;Gaeta et al, 2017;Wen et al, 2017;Vitarelli et al, 2018;Aksu et al, 2019;Hiram et al, 2019). However, few studies have assessed AF associated with LVRAS and dilated left and right atrium, the mechanism of RAF is still remaining unclear.…”
Section: Right Atrial Fibrillation (Raf) and Right Atrialmentioning
confidence: 99%